Antistatic agents in common wear garments, status, and prospects - Ramírez Rodríguez, Julio César
The manufacture of synthetic fibers has innovated the textile industry by providing special properties to improve their performance and usefulness, some of them are technical textiles commonly used at industrial level that use antistatic agents. However, due to the considerable environmental impacts, the use of alternatives that can be applied in everyday garments has been contemplated. Thus, a bibliographic review was made on methodologies, research trends published in databases and verification of their perspectives based on the documentary review methodology, in which Boolean operators were used to optimize the selection of the documents that correlated best with the search. For the results, files were prepared containing all the information that articulates the terms of the research. In the results, it was found that antistatic textiles have been studied from biodegradable polymers with possible properties such as cut resistant, electro conductive, protection from ultraviolet, electromagnetic and radioactive radiation, also opaque fibers to X-rays and visible spectrum radiation are mentioned. Additionally, a methodology was analyzed to determine, in different environmental conditions, the electrical resistance of fabrics in order to estimate the behavior of the different textile materials in relation to static electricity. From this, it is considered that for a better study of the phenomenon of static electricity it is convenient to use the sol-gel preparation (TEOS)